THE CORRELATION BETWEEN KNOWLEDGE AND ATTITUDES OF FEMALE ADOLESCENTS TOWARD BREAST SELF-EXAMINATION - Amalia, Putri; Nuraini , Intan (UNIVERSITAS AIRLANGGA, 2025)
Background: Breast self-examination, known as SADARI, is a self-conducted breast examination to detect any abnormalities in the breasts. In 2020, Indonesia reported 68.858 new breast cancer cases and over 22,000 related deaths (Hamami et al.,2022). This study aimed to determine the relationship between knowledge and the attitude of young women regarding breast self-examination (SADARI) among female students at SMA Sekolah Rakyat Bekasi in 2022. Method: This study utilized descriptive analytic research with a cross-sectional approach using questionnaires conducted at SMA Sekolah Rakyat, Bekasi Regency. Participants consisted of 82 female adolescent respondents, using primary and secondary data. Purposive sampling technique was used with a total population of 103 and a sample of 82, data collection was carried out by distributing questionnaires. Data then analyzed using univariate and bivariate analysis. This study has a dependent variable of attitude and independent variables of knowledge, family support, and information sources. Results: There was a significant relationship between knowledge and the attitude of young women regarding SADARI with a p-value = 0.01 < α = 0.05. There was a significant relationship between family support and the attitude of young women regarding SADARI with a p-value = 0.00 < α = 0.05. There was a significant relationship between information sources and the attitude of young women regarding SADARI with a p-value = 0.00 < α = 0.05. Conclusion: knowledge, information source and family support were significantly correlate to the attitude of young women regarding breast self-examination (SADARI).